Implikatur Tuturan Penutur dan Petutur pada Novel Online Sugar Karya Fit Tri - Niswariyana, Ahyati Kurniamala; Hardi, Rahmat Sulhan; Akhmad, Akhmad; Akbar, M Aris; Afandi, Ahmad (Jurnal Ilmiah Telaah, 2025)
anguage is a tool for communicating and interacting with each other which is applied through speech tools in the form of speech or speech. Every speech spoken by the speaker has a certain meaning and intention in accordance with their respective goals. The study aims to analyze the speech of speakers and speech in the online novel Sugar by Fit Tri. The object of this research is several quotations of speech forms from the speaker and the speech in the novel. The method used in this study is a qualitative method with descriptive analysis. The source of the data is in the form of quotes from the conversations of characters in the novel Sugar. The data collection method uses the watch and record method. Based on the results of the analysis, there are implications of the speaker's speech and speech that emphasizes the theory of implication in the novel Sugar by Fit Tri.